Molecular epidemiology of carbapenem resistant gram-negative bacilli from infected pediatric population in tertiary - care hospitals in Medellín, Colombia : an increasing problem (2016)
ABSTRACT: Background: Gram-negative bacilli are a cause of serious infections in the pediatric population. Carbapenem are the treatment of choice for infections caused by multidrug-resistant Gram-negative bacilli, but the emergence of carbapenem resistance has substantially reduced access to effective antimicrobial regimens. Children are a population vulnerable to bacterial infections and the emergence of resistance can worsen prognosis. The aim of this study is to describe the clinical and molecular characteristics of infections caused by carbapenem-resistant Gram-negative bacilli in pediatric patients from five tertiary-care hospitals in Medellín, Colombia. Methods: A cross-sectional study was conducted in five tertiary-care hospitals from June 2012 to June 2014. All pediatric patients infected by carbapenem-resistant Gram-negative bacilli were included. Clinical information for each patient was obtained from medical records. Molecular analyses included PCR for detection of blaVIM, blaIMP blaNDM, blaOXA-48 and blaKPC genes and PFGE and MLST for molecular typing. Results: A total of 59 patients were enrolled, most of them less than 1 year old (40.7 % n = 24), with a previous history of antibiotic use (94.9 %; n = 56) and healthcare-associated infections - predominately urinary tract infections (31.0 %; n = 18). Klebsiella pneumoniae was the most frequent bacteria (47.4 %), followed by Enterobacter cloacae (40.7 %) and Pseudomonas aeruginosa (11.9 %). For K. pneumoniae, KPC was the predominant resistance mechanism (85.7 %; n = 24) and ST14 was the most common clone (39.3 % n = 11), which included strains closely related by PFGE. In contrast, E. cloacae and P. aeruginosa were prevailing non-carbapenemase-producing isolates (only KPC and VIM were detected in 1 and 3 isolates, respectively) and high genetic diversity according to PFGE and MLST was found in the majority of the cases. Conclusions: In recent years, increasing carbapenem-resistant bacilli in children has become in a matter of great concern. It is important to conduct systemic surveillance and take measures to prevent dissemination of multidrugresistant bacteria.